Survey on utilization of flattening filter-free photon beams in Japan. (25th May 2021) - Kodama, Takumi; Yasui, Keisuke; Nishioka, Shie; Miyaura, Kazunori; Takakura, Toru; Katayose, Tetsurou; Nakamura, Mitsuhiro
Abstract: To understand the current state of flattening filter-free (FFF) beam implementation in C-arm linear accelerators (LINAC) in Japan, the quality assurance (QA)/quality control (QC) 2018–2019 Committee of the Japan Society of Medical Physics (JSMP) conducted a 37-question survey, designed to investigate facility information and specifications regarding FFF beam adoption and usage. The survey comprised six sections: facility information, devices, clinical usage, standard calibration protocols, modeling for treatment planning (TPS) systems and commissioning and QA/QC. A web-based questionnaire was developed. Responses were collected between 18 June and 18 September 2019. Of the 846 institutions implementing external radiotherapy, 323 replied. Of these institutions, 92 had adopted FFF beams and 66 had treated patients using them. FFF beams were used in stereotactic radiation therapy (SRT) for almost all disease sites, especially for the lungs using 6 MV and liver using 10 MV in 51 and 32 institutions, respectively. The number of institutions using FFF beams for treatment increased yearly, from eight before 2015 to 60 in 2018. Farmer-type ionization chambers were used as the standard calibration protocol in 66 (72%) institutions. In 73 (80%) institutions, the beam-quality conversion factor for FFF beams was calculated from TPR 20, 10, via the same protocol used for beams with flattening filter (WFF). Commissioning, periodic QA and patient-specific QA for FFF beams also followed the procedures used for WFF beams. FFF beams were primarily used in high-volume centers for SRT. In most institutions, measurement and QA was conducted via the procedures used for WFF beams.